Proporsionalitas dalam Kebijakan Formulasi Sanksi Pidana - Ali, Mahrus (Jurnal Hukum IUS QUIA IUSTUM, 2018)
This research focused on the idea of proportionality in criminal law and its implementation in the policy of criminal sanctions formulation in legislation. As a normative legal research, this study used a philosophical, conceptual, and statute approach. This study revealed that crime and punishment are an important element of proportionality of criminal law. The higher the crime, the more severe the punishment received by the perpetrators of the crime. In a sanction that integrates both elements, the severity of criminal penalties is based on the proportionality between the seriousness of the crime and the perpetrator's fault with the severity of the potential liability for criminal penalty. The idea of proportionality requires three things: parity, the rank of the seriousness of the crime, and the criminal gap among very serious, heavy, and mild crimes. The policy of criminal sanctions formulation in economic laws has not reflected the idea of proportionality of criminal law. The potential liability for formal crime is more severe than that of material crime. Among similar crimes of bribery, money laundering, and obstruction of justice, the potential liabilities for the penalty are also not proportional. The potential liability for the violations of permits in Banking Law is even more severe than that of corruption. Since the proportionality of criminal law is based on the creation of justice, legislators should rank the seriousness of crimes by using the values in a society as a scale.